Nanotechnology boosts the production of clean energy via nanoparticle addition in anaerobic digestion - Castro, J. Cunha de; Resende, E.; Taveira, Igor; Enrich-Prast, A.; Abreu, F. (Frontiers in Nanotechnology, 2024)
Biogas production via anaerobic digestion is an established and robust technology that produces energy and recycles nutrients. Several biotechnological attempts have been applied to this process to increase biogas production, including adding nanoparticles, but several discrepancies have been reported. To elucidate the contradictory results, we performed a literature review followed by a meta-analysis to evaluate the effect of adding natural nanoparticles to biogas sludge. Our results showed that adding nanoparticles can increase biogas production by up to two orders of magnitude. Considering that, we attribute these results to variability in the nanoparticles applied, leading to less reliable, consistent, and even contradictory results. We observed that the magnetite nanoparticles are the most tested ones with the most promising positive effects. In addition, we observed that concentrations of nanoparticles higher than 100 mg/L can have adverse effects, with an overall decrease in biogas production. The findings in this study highlight the need for a proper characterization of the nanomaterials type and concentration applied to the process to understand the interactions and effects on the microbial communities and dynamics that lead to an overall increase or decrease in biogas yield.